Exchange rates and FDI: Goods versus capital market frictions - Claudia M. Buch; Jörn Kleinert (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2006)
Economic theory provides two main explanations why changes in exchange rates can affect foreign direct investment (FDI). According to a first explanation, FDI reacts to exchange rate changes if there are information frictions on capital markets and if the investment by firms depends on their net worth (capital market friction hypothesis). According to a second explanation, FDI reacts to exchange rate changes if output and factor markets are segmented, and if firm-specific assets are important (goods market friction hypothesis). We provide a unified theoretical framework of the two explanations and test the model using German sectoral data derived from detailed firm-level data. We find greater support for the goods market friction hypothesis.
urn:nbn:de:bsz:21-opus-24374
Keywords: F31; F23; F21; 330; FDI; exchange rates; net worth effects; multinational firms; Wechselkurs; Direktinvestition; Multinationales Unternehmen; Unvollkommener Markt; Theorie; Deutschland